Reliability and validity of the Finnish version of the AO spine PROST (patient reported outcome spine trauma) - Leevi A. Toivonen; Jussi P. Repo; Hannu Kautiainen; Said Sadiqi; Marko H. Neva (Journal of Orthopaedic Surgery and Research, 2025)
Abstract Purpose To translate AO Spine PROST (Patient Reported Outcome Spine Trauma) into Finnish and explore its psychometric properties in a Finnish spine trauma population. Methods Patients were enrolled at an academic level-I trauma center. Score distribution, floor and ceiling effects, and missing items were explored for content validity. Internal consistency, concurrent validity, and reproducibility were explored with Cronbach’s α, exploratory factor analysis, Spearman correlation tests, and Intraclass Correlation Coefficients (ICCs). Results Translation was performed using established guidelines. A sample of 110 patients was enrolled. Score distribution skewed toward higher values, but no floor and ceiling effects were present. Response rates were excellent for all items except for Work/study (60%). Factor analysis indicated two possible dimensions in PROST, explaining 75.3% of the total variance. For PROST total score, correlations were strong with EQ-5D-3 L (r = 0.77 [95% confidence interval: 0.69–0.84]) and ODI (r=-0.89 [0.92–0.84]). Test-retest reliability was excellent with ICC = 0.86 (0.76–0.91). Calculation of the PROST score without the Work/study item appeared valid (ICC 0.99 [0.98 to 1.00]). Conclusions The Finnish version of AO Spine PROST is a reliable and valid measure for spine trauma outcomes. We recommend it for clinical practice and research to reduce the current controversies in spine trauma care.